Towards sustainable development: Alternatives to GDP for measuring progress - Philipp Schepelmann; Yanne Goossens; Arttu Makipaa (Wuppertal Institut für Klima, Umwelt, Energie, 2009)
Economic performance of a country is generally being measured through GDP (Gross Domestic Product), a variable that has also become the de facto universal metric for standards of living. However, GDP does not properly account for social and environmental costs and benefits. It is also difficult to achieve sustainable decision-making aiming at sustainable progress and well-being if welfare is being considered from a purely financial point of view. The study highlights the benefits and some of the shortcomings of GDP. It serves as a helpful and practicable instrument for monetary and fiscal policies. The real problem presumably is that GDP growth is too often confused with (sustainable) welfare growth in people's minds. While there certainly is a correlation between the two, this study shows that this is a highly conditional correlation, void of substantial causality for GDP levels observable in the European Union. In order to be able to assess people's well-being and general sustainable development in the sense of sustainability, an alternative instrument going beyond GDP is necessary. Using so called SWOT analyses, several alternative progress indicators have been assessed in the context of this study. On the one hand it was analysed how far ecological and social factors can be integrated in the GDP measurements. Thereby difficulties arose then trying to monetise these factors. As a further possibility indicators were analysed which are to replace GDP as a whole. The category supplementing GDP seems to be the most realistic and acceptable option for going beyond GDP. Within this approach, GDP is being complemented with additional environmental and/or social information. In order to make this kind of solution feasible the study claims the establishment of an overarching and transparent indicator system for improving economic decision-making in support of sustainable development. – – Wirtschaftlicher Erfolg wird über das Bruttoinlandsprodukt (BIP) eines Landes definiert - eine Größe, die häufig auch als universeller Maßstab für den Lebensstandard gesehen wird. Allerdings erfasst das BIP keine sozialen und ökologischen Kosten- und Nutzen-Effekte. Zudem ist ein Hinsteuern auf Nachhaltige Entwicklung schwer möglich, wenn der Wohlstand allein nach finanztechnischen Gesichtspunkten definiert wird. Die Studie hebt Vorzüge wie Mängel des BIP heraus. Seine Einfachheit und Allgemeingültigkeit machten es zu einem praktikablen Instrument in der Währungs- und Finanzpolitik. Problematisch sei jedoch, dass das BIP von den meisten Menschen mit einem (nachhaltigen) Wachstum von Wohlstand verwechselt wird. Auch wenn es hier Zusammenhänge gibt, so bestehen diese - das hebt die Studie hervor - nur eingeschränkt. Gerade angesichts des BIP-Niveaus in den EU-Staaten besteht keinerlei grundsätzliche Abhängigkeit des generellen Wohlstandsniveaus vom BIP. Um Wohlfahrt und Entwicklung im Sinne von Nachhaltigkeit zu messen, muss demnach ein Instrument jenseits des BIP entwickelt werden. Mit Hilfe von SWOT-Analysen wurden im Rahmen der Studie mehrere alternative Indikatoren für Fortschritt im Sinne von Wohlfahrt analysiert. Zum einen wurde untersucht, inwieweit ökologische und soziale Faktoren in die Messung des BIP einbezogen werden könnten. Hierbei stellte es sich jedoch als Schwierigkeit heraus, diesen Faktoren einen monetären Wert beizumessen. Als weitere Möglichkeit wurden Indikatoren untersucht, die das BIP als Ganzes ersetzen sollen. Als sinnvollsten Weg macht die Studie aus, zusätzlich zum BIP ökologische und soziale Indikatoren einzuführen, die helfen, Informationen zusammenzuführen und sie zusätzlich in Beziehung zu den BIP-Zahlen zu setzen. Die Studie fordert die Einführung eines umfassenden und transparenten Systems von Indikatoren, um wirtschaftliche Entscheidungen im Einklang mit nachhaltiger Entwicklung zu fördern.
urn:nbn:de:101:1-2010050792
Keywords: 330; Nachhaltige Entwicklung; Sozialer Indikator; Sozialproduktskonzept; Kritik